Notes of Some Macroscopic Fungi at IPB University Campus Forest: Diversity and Potency - Ivan Permana Putra; Mega Putri Amelya; Naufal Hafizh Nugraha; Habibah Zam Zamia (Universitas Islam Negeri Mataram, 2019)
Macroscopic fungi is cosmopolitan-heterotrophic organisms which have an important ecological role in ecocystem. The aim of this study was to explore the diversity of species and the potency of Fungi in the Campus Forest of IPB Unversity. Observation was carried out in March to April 2019 using exploration method. Identification used morphological characteristic such as fruit body shape, hygrophnous, cap color, diameter, edge, and margin, wetness level, himenophore type. Result showed that 11 species of macroscopic fungi were identified, divided into 7 families, 4 order, and 1 class. The Group fungi were identified as Termitomyces sp. 1, Termitomyces sp. 2, Marasmius sp. 1, Marasmius sp. 2, Psathyrella sp., Geastrum sp., Stereum sp., Microporus sp., Polyporus sp., Ganoderma sp. 1 and Ganoderma sp. 2. All identified fungi were Basidiomycota. Some fungi found to be potentially used as food source, medicine, and also played an important role as a decomposer in the IPB university campus forest.